STUDI PERENCANAAN KRIB SEBAGAI PENGAMAN TEBING SUNGAI KRUENG ACEH DI DESA CAPEUNG ACEH BESAR - Putri Vinia Jaramenda; Putra Pagihariadi (Racic : Rab Construction Research, 2024)
Sand dredging activities in the Krueng Aceh river, which is the main and largest river in the Aceh Besar Regency and Banda Aceh City, causes degradation of the bottom of the Krueng Aceh River which can trigger the collapse of river banks.Therefore, a study was carried out on planning the construction of krib as an alternative building that could protect the banks of the Krueng River in Aceh from water scouring which occurs especially during floods. The location of this planning study is located in Capeung Village, Seulimuem District, Aceh Besar Regency. The data used in this planning study includes rainfall data, topographic maps, soil mechanics data and maps of the Krueng Aceh watershed. Calculations carried out in this planning study include calculating rainfall and planned flood discharge, krib construction planning and krib stability analysis. The planned krib construction has a length of 5 meters and the distance between the krib is 10 meters. The height of the krib at the base is 0.75 meters and at the ends 0.5 meters. The construction of the krib is planned to be inclined towards the upstream by 10o, the slope of the krib protection layer is 1:2.5 and the slope of the lighthouse krib is 1:20. The soil at the location where the krib is planned is capable of withstanding the weight of the entire krib construction and the krib construction is safe against shear forces and overturning moments.